Familiar Locations and Similar Activities: Examining the Contributions of Reliable and Relevant Knowledge in Offenders’ Crime Location Choices - Curtis-Ham, Sophie (International criminal justice review, 2025)
This paper examines the recently theorized roles of the reliability and relevance of offenders’ knowledge of locations in their crime location choices. Using discrete choice models, we analyzed offenders’ pre-offense activity locations from police data (home addresses, family members’ home addresses, work, school, prior offenses, victimizations, non-crime incidents, and other police contacts) and 17,054 residential burglaries, 10,353 non-residential burglaries, 1,977 commercial robberies, 4,315 personal robberies, and 4,421 extra-familial sex offenses, in New Zealand. Offenders were most likely to offend where their prior activity locations indicated they had highly reliable and highly relevant knowledge—where they were both highly familiar with the area and had conducted similar activities—and less likely where offenders had less familiarity or less similar activities. The results support a recent extension of crime pattern theory and highlight the importance of including both reliability and relevance factors when modeling or predicting offenders’ crime location choices.